Predictors of failure after single faecal microbiota transplantation in patients with recurrent Clostridium difficile infection: results from a 3-year, single-centre cohort study. (May 2017) - Ianiro, G.; Valerio, L.; Masucci, L.; Pecere, S.; Bibbò, S.; Quaranta, G.; Posteraro, B.; Currò, D.; Sanguinetti, M.; Gasbarrini, A.; Cammarota, G.
Abstract: Objectives: Faecal microbiota transplantation (FMT) is an effective treatment for recurrent Clostridium difficile infection (CDI). Although a single faecal infusion is usually sufficient to eradicate CDI, a considerable number of patients need multiple infusions to be cured. The aim of this study was to identify predictors of failure after single faecal infusion in patients with recurrent CDI. Methods: We included patients with recurrent CDI prospectively treated with FMT by colonoscopy. By means of univariate and multivariate analysis, variables including female gender, age, number of CDI recurrences, severity of CDI, hospitalization, inadequate bowel preparation, unrelated donor, and use of frozen faeces, were assessed to predict failure after single faecal infusion. Results: Sixty-four patients (39 women; mean age 74 years) were included. Of them, 44 (69%) were cured by a single faecal infusion, whereas 20 (31%) needed repeat infusions. Overall, FMT cured 62 of 64 (97%) patients. In the subgroup of patients with severe CDI, only eight of 26 (30%) were cured with a single infusion. At multivariate analysis, severe CDI (OR 24.66; 95% CI 4.44–242.08; p 0.001) and inadequate bowel preparation (OR 11.53; 95% CI 1.71–115.51; p 0.019) were found to be independent predictors of failure after single faecal infusion. Conclusions: Severe CDI and inadequate bowel preparation appear to be independent predictors of failure after single faecal infusion in patients treated with FMT by colonoscopy for recurrent CDI. Our results may help to optimize protocols and outcomes of FMT in patients with recurrent CDI.